Regulasi Penyelenggaraan Polis Digital dalam Kerangka Perlindungan Hukum Bagi Perusahaan Asuransi dan Nasabah - Kadek Ary Purnama Dewi (Jurnal Preferensi Hukum, 2025)
Law Number 40 of 2014 concerning Insurance does not provide a definition of an insurance policy nor regulate the use of electronic or digital policies. In this context, the Financial Services Authority (OJK) holds the authority to establish a sound financial industry and to protect individuals who utilize insurance services. This study aims to identify and analyze the legal obligations of insurance companies in implementing digital policies and in providing protection for insurance customers under such policies. The research employs a normative legal method, focusing on the study of laws and regulations relevant to the issue. The findings indicate that the legal obligations of insurance companies in implementing digital policies are stipulated in the Regulation of the Financial Services Authority of the Republic of Indonesia Number 8 of 2024, which mandates that Insurance Companies or Sharia Insurance Companies must provide access for Policyholders, Insured Parties, or Participants to obtain and/or print copies of their Insurance Policies. Furthermore, when the Insurance Policy is issued and delivered in electronic form, the company is prohibited from requiring a printed version of the policy as part of the claim submission documents. Regarding the legal protection of insurance customers in digital policies, OJK is authorized to provide such protection by implementing preventive measures to avoid consumer losses, including safeguarding customers who use electronic or digital policies. Under the Consumer Protection Law, customers are entitled to advocacy, protection, and dispute resolution mechanisms in cases of conflicts related to electronic policies between policyholders and insurance companies.